Potensi Inovasi untuk Meningkatkan Kesejahteraan Masyarakat Desa - Arif Sofianto (Research and Development Agency Ministry of Home Affairs, 2020)
The village have many dilemmas. Villages face a dilemma of many resources but low welfare despite high natural resource exploitation. Innovation is one of the important keys for village communities to solve these problems. This research was aimed to 1) Identifying the potential of village resources through innovation; 2) Identifying protection campaigns; 3) Analyze the key factors for the development of innovation in Central Java. This is a qualitative descriptive study, conducted in 22 villages which has a high poverty rate, but has a large potential resources. The research involved informants from the village head, village administration apparatus, and community group representatives. Data collection using interviews, questionnaires, adn FGD. Data analysis using Miles and Huberman techniques. The conclusions of this study are: 1) Natural, human, social and economic resources that are managed in new ways through tourism activities, creative industries, and postharvest product processing. 2) Innovation constrained of limited ideas, lack of pioneering and entrepreneurial spirit, limited knowledge and technology, low community participation, and weak role of village institutions. 3) Key factors that drive the development of innovation are the existence of pioneering figures who are willing to take risks and have different ideas and are supported by the village government by involving relevant stakeholders